The Rise of Artificial Intelligence: Friend or Foe of Economic Growth? - YOLUSEVER, ARAS (Gökhan Tuncel, 2025)
Artificial Intelligence (AI) is fundamentally altering the global economic landscape, unveiling both remarkable growth opportunities and significant challenges. As a pivotal technology of the 21st century, AI is set to revolutionize productivity, catalyze innovation, and spawn entirely new sectors within the economy. Its applications extend across various industries—including healthcare, manufacturing, finance, and logistics—where it streamlines operations and enables advancements that were previously inconceivable. However, the transformative power of AI is accompanied by critical concerns. Potential job displacement resulting from automation, the exacerbation of economic inequality, and ethical considerations surrounding AI deployment remain pressing issues. This analysis delves into the complex and dualistic impact of AI on economic growth, focusing on its ability to enhance productivity and drive innovation while also examining the implications for the labour market and the regulatory framework needed to address these challenges. This discussion evaluates AI's dual role in driving economic prosperity and posing risks to inclusive, sustainable growth. Ultimately, it questions whether AI will be an ally or adversary in achieving equitable economic development.
Keywords: Artificial Intelligence; Economic Growth; Productivity; Innovation; Labor Market